2009
DOI: 10.3763/inbi.2009.0004
|View full text |Cite
|
Sign up to set email alerts
|

Control strategies for lighting and ventilation in offices: effects on energy and occupants

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 30 publications
(21 reference statements)
0
14
0
Order By: Relevance
“…Although indoor temperature (and humidity) will inevitably be higher than the householder's default preference during events, there is little evidence of substantial discomfort penalties [Greenberg & Straub, 2008;Summit Blue 2004;Kirby, 2003]. This may be because the temperature rise is slow and is not perceived over the few hours of the event [Newsham et al, 2009], or because occupants are willing to tolerate the higher temperatures in the context of the threat to grid stability. Nevertheless, there is evidence that override rates do increase as the length of service curtailment increases [Greenberg & Straub, 2008;KEMA, 2006;Kirby 2003].…”
Section: Discussionmentioning
confidence: 99%
“…Although indoor temperature (and humidity) will inevitably be higher than the householder's default preference during events, there is little evidence of substantial discomfort penalties [Greenberg & Straub, 2008;Summit Blue 2004;Kirby, 2003]. This may be because the temperature rise is slow and is not perceived over the few hours of the event [Newsham et al, 2009], or because occupants are willing to tolerate the higher temperatures in the context of the threat to grid stability. Nevertheless, there is evidence that override rates do increase as the length of service curtailment increases [Greenberg & Straub, 2008;KEMA, 2006;Kirby 2003].…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies that simply examine both data types include Altomonte and Schiavon [83], Geng et al [84] and Newsham et al [85]. Altomonte and Schiavon [83] studied the difference between BREEAM and non-BREEAM office buildings using survey data on lighting, acoustic and thermal comfort which were collected while spot measurements of various IEQ parameters were collected at the respondent's workstation.…”
Section: Outcomes Gap: Measured Vs Experiencedmentioning
confidence: 99%
“…Geng et al [84] compared environmental measurements, survey results and productivity tests under various air temperature conditions from 16 • C to 28 • C. Interestingly, they found that thermal dissatisfaction appeared to override awareness of other IEQ parameters like lighting, noise and IAQ, but when occupants were thermally comfortable, they became more aware of these parameters, specifically, noise and lighting, demonstrating the interconnectedness of the IEQ perceptions and primacy of thermal comfort. A laboratory-based study by Newsham et al [85] used occupant surveys to evaluate occupant attitudes to having personal control over the changing environmental conditions that would occur during a demand response event. They found that the ability to control one's lighting and ventilation levels both increased satisfaction and decreased energy use.…”
Section: Outcomes Gap: Measured Vs Experiencedmentioning
confidence: 99%
“…During direct control periods, indoor temperatures were likely higher than preferred, but occupants appeared to largely accept and tolerate these. One explanation for this is that indoor temperature increases slowly and such changes may not be perceived, or at least not until several hours into the event [23]. Alternatively, occupants may perceive the change in temperature and comfort, but be willing to tolerate it as a trade-off in exchange for greater grid stability or energy efficiency.…”
Section: Defaults In Smart Technologiesmentioning
confidence: 99%
“…A third explanation for default effects focuses on social norms and implied endorsement from others [21][22][23]31]. From this perspective, the default conveys the socially desired behavior [14,32].…”
Section: Why Do Defaults Work?mentioning
confidence: 99%